A retrospective analysis of controlled active motion (CAM) versus modified Kleinert/Duran (modKD) rehabilitation protocol in flexor tendon repair (zones I and II) in a single center: handsurgery - Wirtz, C.; Leclère, F. M.; Oberfeld, E.; Unglaub, Frank; Vögelin, E. (Archives of orthopaedic and trauma surgery, 2023)
The aim of this study was to analyze primary flexor tendon repair results in zones I and II, comparing the rupture rate and clinical outcomes of the controlled active motion (CAM) protocol with the modified Kleinert/Duran (mKD) protocol.
Online veröffentlicht: 17. August 2022
Gesehen am 06.08.2024